FET circuit model extraction and characterization for monolithic microwave integrated circuit design - Agustin, Rowelito D.; Dizon, Raphael Angelo S.; Sebastian, Michael James D. (2008.)
The use of Gallium Arsenide field-effect transistors in high frequency applications has been a remarkable advancement in microwave technology. More research and development groups are now giving much attention to the design and fabrication of GaAs FETs for different RF applications. This posts a demand for a reliable method of characterizing and extracting small and large signal circuit models for the transistor. In this project, small-signal and large-signal circuit models of Gallium Arsenide field-effect transistor devices are extracted using de-embedded S-parameter measurements and DC-IV data. A conventional FET equivalent circuit model is used in small-signal modeling and the Curtice Quadratic model is employed in large-signal modeling. Parameter extraction is performed to generate the initial set of equivalent circuit component values. The small-signal models are simulated using Ansoft Designer SV and the resulting S-parameters are compared to the measured de-embedded S-parameters. In large-signal modeling, simulations are done using Universal Circuit Simulator software. The actual DC-IV curves are compared to the simulation results. Optimization using Sequential Simplex method is implemented to minimize the errors between measured and simulated data. Deviations between optimized small-signal models and de-embedded data were observed to be reduced compared to errors present between the initially extracted model and de-embedded S-parameter measurements. The magnitude errors of the optimized small-signal model were minimized by 35% for both AM006MX and ATF-35143 transistors. And the phase differences were reduced to about 33% and 25% for AM006MX and ATF-35143 respectively. Also, deviations between the optimized Curtice model and measured DC I-V characteristics showed reduced drain-source current errors. For the optimized large-signal model, the average current errors for AM006MX were minimized by 63% and 50% based on the Ids-Vgs and Ids-Vds curves correspondingly. The DC characterization and small-signal parameter extraction performed was an effective method of extracting the initial component values that can be used in circuit model optimization. Also, the Sequential Simplex Optimization was a useful algorithm in providing minimized errors between the actual and simulated measurements. The optimized models of the field-effect transistors can be utilized in designing and implementing Monolithic Microwave Integrated Circuits such as low-noise amplifiers.
Undergraduate Student Project (B.S. ECE)--University of the Philippines, Diliman.
Keywords: Field-effect transistors; Integrated circuits -- Design and construction; Microwave integrated circuits -- Design and construction; FET circuit model extraction; Monolithic Microwave Integrated Circuits